FARMERS' GROUP RESPONSE TO THE HEALTHY RICE CULTIVATION PROGRAM (BTS) IN SAKRA DISTRICT, EAST LOMBOK DISTRICT - ernawati (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2024)
The responses given by farmer groups to the rice healthy plant cultivation (BTS) activity program are in the form of cognitive responses, affective responses, conative responses to achieve goals by participating in activities in the planning, implementation, monitoring and evaluation stages. The aim of this research is to analyze: 1) Stages of activities in the healthy rice cultivation (BTS) program in Sakra District. 2) Responses given by farmer groups to the rice healthy plant cultivation (BTS) program in Sakra District. 3) Factors that influence the formation of farmer groups' responses to the healthy rice cultivation (BTS) program in Sakra District. The basic research method is descriptive. Location determination was carried out deliberately in Sakra District by taking 30 respondents. Responses in this study were measured using scoring analysis. Meanwhile, to measure factors using Chi Square analysis. The research results show that: 1) There are 3 stages in implementing the healthy rice cultivation (BTS) program in Sakra District, namely the first is the preparation stage, the second is the implementation stage, the third is the monitoring and evaluation stage. 2) farmers' responses to activities are in the medium category with an average value of 2. 3) there is no influence between the factors age, education and non-farming income and cognitive responses. Age, education, land area and off-farm income with affective responses and age and off-farm income with conative responses. Meanwhile, there is an influence between land area factors and cognitive response. Education and the future of land with the conative response given by farmer groups to the rice healthy plant cultivation (BTS) program in Sakra District, East Lombok Regency.